Synthesis of some 2-aryl-4-(7’-hydroxy-4’-methyl-coumarin-6’(or-8’)-yl)-2,3-dihydro-1H-1,5-benzodiazepines. - Thanh, Nguyen Ngoc; Thao, Nguyen Minh (Vietnam Journal of Chemistry, 2012)
Thirteen new compounds type 2-aryl-4-(7’-hydroxy-4’-methylcoumarin-6’(or-8’)-yl)-2,3-dihydro-1H-1,5-benzodiazepines have been synthesized from α,β-unsaturated ketones of 6(or-8)-acetyl-7-hydroxy-4-methylcoumarin by reaction of corresponding α, β-unsaturated ketones with o-phenylenediamine. The structures have been determined and their biological activity has been investigated.